(untitled) (Advancements in Homeopathic Research, 2025)
Urolithiasis, renal stones, kidney stones are used interchangeably to refer to the accretion of hard, solid , non metallic minerals in urinary tract. Different regions of India have varying stone compositions, however there aren’t many extensive prospective studies to offer accurate figures.Males are more likely than females to develop urinary stones at all ages. Calcium oxalate is the most common component of urinary stones in Northwestern Rajasthan, regardless of age group. Calculi that are associated with obstruction, renal failure, and infection requires further critical interventions.Treating urolithiasis through organopathic prescription in homoeopathy can beneficial to avoid unwanted complications as in modern line of treatment. Solanum Xanthocarpum, an unexplored drug in field of homoeopathy has shown beneficial results in treating calculi in other systems of medicine. Charak has recommended its use in piles, cough, delirium tremens and calculi expulsion. Shushruta has found its effectiveness in ophthalmia and urinary strictures. Bangasena has recommended its use in cough of children. According to Dr. SC Ghosh Solanum Xanthocarpum is unquestionably a grand medicine in suppression of urine, stricture and calculi explusion and formation. In the cure of these maladies, Solanum Xanthocarpum can be compared with Berberis Vulgaris, Cantharis, Sarsaparilla and lycopodium. This case report enhances the knowledge regarding Solanum Xanthocarpum, its constituents and its beneficial results clinically in treating patient suffering from urolithiasis which is evident through investigations reports of the patient.